Determinasi Faktor Biologis dan Kontekstual Terhadap Keterlambatan Rujukan Maternal Berisiko di Kabupaten Lombok Tengah - Baiq Wiwik Yastuti; Lalu Sulaiman; Lalu Abdul Khalik (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aimed to identify biological and contextual determinants influencing maternal referral delays at Praya Regional Hospital, Central Lombok Regency. Referral delays significantly contributed to increased risks of maternal complications and mortality, particularly in areas with limited access to healthcare services. A quantitative cross-sectional design was used, and the sample included 95 pregnant women referred to Praya Hospital. Data were obtained through a structured questionnaire and analyzed using Chi-Square tests and binary logistic regression to determine associations between variables and to identify the most dominant factor. The analysis showed that administrative barriers had a significant association with referral delays (p = 0.001), while other variables such as trust (p = 0.383), healthcare provider readiness (p = 0.084), and indirect costs (p = 0.005) showed no significant associations. Administrative barriers were identified as the strongest determinant, with an odds ratio (OR) of 8.037 (95% CI: 3.044–21.221; p = 0.000). To accelerate maternal referral processes, simplifying administrative procedures and implementing digital systems such as SISRUTE were strongly recommended. Further studies are recommended to evaluate the effectiveness of technology-based referral system reforms in reducing maternal mortality rates, especially in resource-limited settings.